Reproducibility of a quantitative system for assessing the quality of diagnostic ultrasound - Iared,Wagner (2018)
Abstract Objective: To present a quantitative system for assessing the quality of ultrasound examinations-SQUALUS-and to determine its reproducibility, taking into consideration the images on file, as well as the consistency between the images obtained and the final report. Materials and Methods: The system includes questions related to the number of images; the appropriateness of images in relation to the protocol established; focus adjustment; depth; gain; and appropriateness of the measurements for B-mode examinations. For Doppler examinations, the system includes questions related to the appropriateness of color images, the spectral analysis, and correction of the insonation angle. To assess the quality of the report, the system includes questions related to the consistency between the images obtained and the contents of the report. An overall numerical score was assigned by averaging the scores for image quality and for the contents of the report. Two independent examiners, each blinded to the evaluation of the other, assessed 30 different types of ultrasound examinations. Results: There was statistically significant agreement between the two examiners for 8 of the 10 questions related to image quality. For the questions related to the quality of the reports, the interexaminer agreement was almost perfect. Conclusion: The proposed quantitative system for assessing the quality of ultrasound examinations is a reproducible tool that can be used in audits and accreditation programs.